The Relationship between Environmental Change and Socio-Economic Structures in the Context of the Socio-Ecological System Approach in Turkey - Kozaman, Senem; Sengezer, Betul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2013)
The aim of the paper is to understand the spatial structure of development in Turkey in the context of socio-economic components and environmental change and to exhibit the interaction between these variables. Accordingly, using factor analysis and k-means cluster analysis with the contribution of environmental, social and economic indicators, different geographical patterns are revealed in Turkey. Interaction between natural degradation and socio-economic structure is also examined with the index of SES components in resulting sub-regions. Based on research findings, the rate of development in developing and underdeveloped regions is increasing faster than in metropolitan areas. From this determination it's possible to draw three conclusions: (1) it's impossible to mention sustainability in metropolitan areas if development proceeds in environment and natural resources, (2) the continuity of growth in developing regions along with the contribution of institutional, social and physical capital will enhance the potential of sustainable development, (3) despite the decrease in resource consumption and the development in economic and human capital in tourist centres, the deterioration of natural resources that are the basis of tourist activities exposes risks for balanced growth in these centres.
Keywords: Architecture